Sugars as supplemental cryoprotectants for marine organisms. (4th February 2017) - Tsai, Sujune; Chong, Gabriella; Meng, Pei‐Jie; Lin, Chiahsin
Abstract: Cryopreservation has been extensively used in various mega‐industries and has recently been applied in genetic banking for conservation purposes. Compared with conventional cell preservation methods, cryopreservation can maintain the viability of cryopreserved cells for an indefinite time at a relatively lower cost and lesser manpower, with lower probabilities of contamination and genetic changes. This study presents the crucial role of sugar, a cryoprotectant supplement in cryopreservation. Sugar molecules typically interact with the lipid bilayer during the freezing phase to maintain plasma membrane integrity when cells undergo dehydration. When combined with other permeable cryoprotectants such as glucose with methanol and trehalose with dimethyl sulphoxide, sugar prolongs and enhances cellular post‐thaw viability. Moreover, terrestrial and marine organisms have benefited from the inclusion of sugar in the cryopreservation protocol. For wide range of cells such as the sperm, oocytes, embryos and larvae of marine vertebrates and invertebrates, as well as marine algae, cryopreservation with sugar produced positive results compared with cryopreservation without sugar. Not all sugar is beneficial, and the type and concentration of sugar should be applied according to the species. Moreover, the freezing method may also affect the function of sugar. Nevertheless, understanding the role of sugar in cryobiology and conducting a preliminary trial of sugar for cryopreserving cells would benefit future research on cryopreservation.